(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
In the last 30 years, Iraq’s economic involvement in the world market has dramatically fluctuated— fluctuations brought, in part, by damage in the infrastructure during the Iran-Iraq War of the 1980s, followed by a multinational military response and years of economic sanctions as a result of its invasion to Kuwait in 1990. In the seventies of the last century the Iraqi public sector was taking the responsibility for most of the activities of exports and imports. The main exports products in Iraq were crude oil, which formed the average between (8 4% to 96%) of the total Iraqi exports in most of years. Iraq government established some of the industries mainly for exports, such as; oil products, Petro chemistry, fertilizer, and cement industry. In the early of the 1980s when the first Gulf War started between Iraq and Iran , most of these industries stopped, as a result of war and the Iraqi economy transformed to war economy. This situation continued until the early 1990s, when the second Gulf War started and its consequences on Iraqi economy by imposing the economic embargo , which continued until 2003. Over than 30 years, the trade policy in Iraq was bound, the law of the tariff number (77) for the year 1955 and its updates, which has been considered as one of the highest level of tariff laws. The most important restrictions was getting import license that allowed government to controll the imports. For instance, it was not possible to import a private car without import license, which was not provided to everyone he can get it only for very special cases, and the tariff level was vary according to the origin of the car and may it reach up to 300% of the value of the car.